2021
DOI: 10.1038/s41467-021-27565-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow dark current in near-infrared perovskite photodiodes by reducing charge injection and interfacial charge generation

Abstract: Metal halide perovskite photodiodes (PPDs) offer high responsivity and broad spectral sensitivity, making them attractive for low-cost visible and near-infrared sensing. A significant challenge in achieving high detectivity in PPDs is lowering the dark current density (JD) and noise current (in). This is commonly accomplished using charge-blocking layers to reduce charge injection. By analyzing the temperature dependence of JD for lead-tin based PPDs with different bandgaps and electron-blocking layers (EBL), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 63 publications
(59 reference statements)
2
78
0
Order By: Relevance
“…The mean J D values are reproduced over several devices (Figure S2, Supporting Information).These values are almost one order of magnitude lower than the ones measured for 3D perovskites CsFAMA and FAMA (1 × 10 −6 and 6 × 10 −7 mA cm −2 , respectively) and are ranked among the lowest reported in the literature for quasi‐2D and 3D PPDs. [ 8,9,16,17,24 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean J D values are reproduced over several devices (Figure S2, Supporting Information).These values are almost one order of magnitude lower than the ones measured for 3D perovskites CsFAMA and FAMA (1 × 10 −6 and 6 × 10 −7 mA cm −2 , respectively) and are ranked among the lowest reported in the literature for quasi‐2D and 3D PPDs. [ 8,9,16,17,24 ]…”
Section: Resultsmentioning
confidence: 99%
“…This approach enables EQEs ≈80% and spectral responsivity (SR) ≈0.4 A W −1 (Figure S9, Supporting Information). The interfacial energy Φ of such combinations is in fact maximized beyond that of PPDs employing only 2D–3D perovskites due to deep EBL HOMO energy (≈−5.45 eV for PTAA:poly‐TPD compared to −5.2 eV for PTAA [ 9 ] ) and the J D is suppressed to extremely low values. A reproducible and record‐low J D of 1 × 10 −8 mA cm −2 and ≈5 × 10 −9 mA cm −2 at −0.2 V was measured for BA < n > = 4 and 5, respectively (Figure 5a; Figure S10, Supporting Information) based on constant voltage measurements over time at discrete biases (Figure S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy levels of the perovskite layer are previously reported in literature. 45 PEDOT:PSS and C 60 /BCP were chosen as hole and electron transport layers, respectively, as they have shown to be good candidates for these roles in Sn–Pb based solar cells. 46 Usually, ITO top electrodes are processed by ion sputtering which can easily damage any soft organic underlayers, 47 leading to increased leakage current, as well as reduced efficiency and lower lifetime of the device.…”
Section: Resultsmentioning
confidence: 99%
“…Recently it has been shown that the origin of the dark current in perovskite photodetectors is due to the interfacial energy offset between the perovskite and the electron blocking layer (EBL). 45 Carefully choosing an EBL with a lower highest occupied molecular orbital (HOMO) than PEDOT:PSS ( e.g. poly(4-butyl- N , N -diphenylaniline) (poly-TPD)) could further improve the J D of these devices and will be subject of further study.…”
Section: Resultsmentioning
confidence: 99%